Early exfoliation as an indication for evaluation: A case report - J Reni Anjalin; S Ramasamy; R Madhavan Nirmal (Wolters Kluwer Medknow Publications, 2020)
Hypophosphatasia (HPP) is a rare genetic skeletal disorder that occurs due to mutation in the ALPL gene. It is characterized by defective bone and teeth mineralization. Odontohypophosphatasia is the mildest form of HPP that affects only the dental tissues, manifests as early exfoliation of teeth, defective cementum formation, reduced alveolar bone height, and enlarged pulp chamber. We report a case of an 8-year-old female who presented only with dental findings of HPP. HPP was suspected due to reduced serum alkaline phosphatase level, reduced alveolar bone height, and enlarged pulp chamber. The cemental defects were identified by the ground section of the exfoliated tooth and measured using Image J software. Thus, we arrived at the final diagnosis of Odontohypophosphatasia.